Penggunaan Balutan Modern Memperbaiki Proses Penyembuhan Luka Diabetik - Lestari Ismail, Dina Dewi Sartika; Irawaty, Dewi; Haryati, Tutik Sri (Jurnal Kedokteran Brawijaya, 2009)
ABSTRACTDiabetes mellitus is a chronic carbohydrate metabolism disturbance with many long term complications. Oneof its complications is diabetic wound risk to amputation. Wound care is nursing intervention aimed to preventthe risk of amputation. A cost effective evaluation is needed to identify the most benefecial wound care. Aquasi-experiment comparing modern and conventional with pretest and post test with control group designwas conducted with 16 selected patients. The outcome measure is wound healing process score based onBates-Jansen wound assessment while the cost measured is wound care material cost. An independent t testwith 95% confidence interval was performed to evaluate the difference of healing process and cost effectivitybetween modern and conventional dressing. The result showed a significant differences of healing processscore (p=0,002) and cost effectivity (p=0,031) between modern and conventional dressing application fordiabetic wound. It can be concluded that the application of modern dressing significantly improve the healingprocess in diabetic wound but with higher treatment cost.Keywords : Diabetic wound, Modern Dressing, Healing Process, Cost Effectivity Care